Recommended Guidelines, Practical Information and Personal Accounts - Israel, Gianna; Tarver, Donald (Philadelphia PA, 1997)
By empowering clients to be well informed medical consumers and by delivering care providers from the straitjacket of inadequate diagnostic standards and stereotypes, this book sets out to transform the nature of transgender care. In an accessible style, Gianna Israel and Donald Tarver discuss the key mental health issues, with much attention to the vexed relationship between professionals and clients. They propose a new professional role, that of the "Gender Specialist." The authors have also provided useful listings of organizations, centers, and World Wide Web sites. Transgender Ca.; Includes bibliographical references and index.; Part I. Recommended guidelines -- part II. Essays.; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Electronic books; Transgender people -- Medical care; Transgender people -- Mental health services; Người chuyển giới -- Chăm sóc sức khỏe